2015
DOI: 10.1007/s13358-015-0070-5
|View full text |Cite
|
Sign up to set email alerts
|

Digital endocranial cast of Pampatherium humboldtii (Xenarthra, Cingulata) from the Late Pleistocene of Uruguay

Abstract: The diversity of the order Cingulata is much higher in the fossil record than that represented by the extant species. While pampatheres, one of its extinct groups, are superficially similar to armadillos, recent phylogenetic analysis grouped them with glyptodonts in the clade Glyptodonta. We describe here the first digital endocranial cast of a pampathere, Pampatherium humboldtii, from the Late Pleistocene of Uruguay and compare its morphology with that of glyptodonts and extant and fossil armadillos. Some of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 19 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…I therefore propose to reassign PIMUZ A/V 428 and PIMUZ A/V 430 to Pa. humboldtii . While the cranial and endocranial material is relatively well-studied for this species (e.g., Ferreira et al, 2018 ; Tambusso & Fariña, 2015a ), the postcranial remains are poorly known. PIMUZ A/V 428 offers the opportunity to analyze several complete long bones of Pa. humboldtii .…”
Section: Resultsmentioning
confidence: 99%
“…I therefore propose to reassign PIMUZ A/V 428 and PIMUZ A/V 430 to Pa. humboldtii . While the cranial and endocranial material is relatively well-studied for this species (e.g., Ferreira et al, 2018 ; Tambusso & Fariña, 2015a ), the postcranial remains are poorly known. PIMUZ A/V 428 offers the opportunity to analyze several complete long bones of Pa. humboldtii .…”
Section: Resultsmentioning
confidence: 99%
“…2023), Primates, Chilecebus carrascoensis (Ni et al . 2019), and Xenarthra (Tambusso & Fariña 2015a, 2015b). All fossils included in the quantitative analyses are known from published virtual endocasts except Do.…”
Section: Methodsmentioning
confidence: 99%
“…Although the cranial anatomy is relatively well known in xenarthrans, their internal cranial anatomy remains poorly studied. Yet, several studies have shown that their exploration provides systematic interest on their past and present diversity (Zurita et al, 2011;Fernicola et al, 2012;Billet et al, 2015;Tambusso & Fariña, 2015a;Tambusso & Fariña, 2015b;Billet et al, 2017;Boscaini et al, 2018;Boscaini et al, 2020;Tambusso et al, 2021). In a recent study (Le Verger et al, 2021), we describe and compare 8 cranial canals (involved in the vascularization and innervation of the cranium) and alveolar cavities (Figure 1) of 30 specimens belonging to the Cingulata.…”
Section: Introductionmentioning
confidence: 99%